Search for TeV emission from the Fermi Bubbles at low Galactic latitudes with H.E.S.S. inner Galaxy survey observations - Moulin, Emmanuel; Montanari, Alessandro; Spencer, Samuel; Malyshev, Denys; Malyshev, Dmitry; Abdalla, H.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; et al. (Proceedings of Science, 2022)
The Fermi Bubbles were discovered about a decade ago in the Fermi-LAT data as a double-lobe structure extending up to 55° in Galactic latitudes above and below the Galactic Center. At the moment their origin is still unknown. The H.E.S.S. collaboration is currently performing the first ever survey in TeV gamma rays of the Milky Way inner region: the Inner Galaxy Survey. This survey is intended to achieve the best sensitivity to faint and diffuse emissions in a region of several degrees around the Galactic Centre. It provides an unprecedented sensitivity to dark matter signals, new diffuse emissions, and TeV outflows from the Galactic Centre. Understanding the properties of the Fermi Bubbles at low Galactic latitudes will provide key insights into their origin. We search for TeV emission at the base of the Fermi Bubbles using low-latitude spatial templates. The first results obtained with the 2014-2020 H.E.S.S. observations will be reported.
CRIS-Team Scopus Importer:2022-12-23